IDENTIFIKASI STATUS NUTRISI DAN RESIKO MALNUTRISI PADA LANJUT USIA DI PANTI SOSIAL TRESNA WERDHA MINAULA KOTA KENDARI - Nurfantri; Yuniar, Dian (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2016)
In Indonesia in 2013 reached 8.9% of the total population of 250 million inhabitants. Thepurpose of this study was to determine the nutritional status of the elderly in Social InstitutionsTresna Werdha Minaula Kendari City in 2016. The research was conducted in Social InstitutionsTresna Werdha Minaula Kendari City starting on May 24 until May 30, 2016. The method usedin this study is survey descriptive . The population in this study were all elderly residing in TresnaElderly Social Institution Minaula Kendari many as 95 people. These samples included 56 peoplewith a sampling technique that total sampling. Results of research on the nutritional status of theelderly are the normal nutritional status to 34 persons (60.7%), the malnutrition status is 21people (37.5%), and the nutritional status of more that 1 (1.8%). Risk of malnutrition elderly bythe Mini Nutritional Assessment (MNA) is on good nutrition that 22 (39.3%), on the status of riskof malnutrition is 33 people (58.9%), and the malnutrition that is 1 (1.8%) , Carers are expectedto always pay attention to the nutritional status of the elderly in nursing so that it can be fulfilledproper nutrition for the elderly. Future studies are expected to develop similar research withother variables relevant, such decreased organ function and nutrition of elderly, elderly nutritionpattern processing, functional disorders and diseases of the elderly nutrition.